Preliminary Study On the Function-Defining 3D Surface Roughness Parameters in Tangential Turning - Sztankovics, István (International Journal of Integrated Engineering, 2023)
The function-defining three-dimensional (3D) surface roughness parameters (which describe an aspect of the surface quality based on areal topography measurements) are studied on tangentially turned surfaces with different technological parameters in this paper. The 23 factorial design is applied in the planning of experiments. Two levels of depth of cut, cutting speed and feed were chosen for the comprehensive analysis of the tangential turning process. The values of Core Roughness, Reduced Peak Height, Reduced Valley Depth, Skewness and Kurtosis are measured by the application of a 3D areal roughness measurement machine. Equations were determined for the calculation of the studied parameters according to the factorial design method. The results were evaluated in two steps: first the functional parameters derived from the Areal Material Ratio curve were analyzed, then the Skewness and Kurtosis of the assessed area were studied. It is found that a two-fold increase in the cutting speed decreases the Core Roughness Depth, Reduced Peak Height, and Reduced Valley Depth 2-4-fold. The increasing feed rate lowers the presence of inordinately extremes, resulting in a smoother surface. In the point of view of Skewness and Kurtosis, lower cutting speeds and higher feeds are more favorable.